Road Vehicle Following System With Adaptive Controller Gain Using Model Reference Adaptive Control Method - M. R., Sapiee; Sudin, Shahdan (United Kingdom Simulation Society, 2010)
In order to maintain stability and satisfy operating constraints, the control system on the following vehicle needs information about the motion of preceding vehicle. A one-vehicle look-ahead control strategy is proposed and will be investigated for this operation. A mathematical model for this control strategy is obtained and simulated. This paper describes the process of designing an adaptive controller gain for a road vehicle following system. This is done through simulations and is further discussed to find the effectiveness of the method.